Deaths in jail: a retrospective analysis of autopsies performed at the Legal Medicine Unit of Pavia (1999-2022) - Belli, Giacomo; Romão, Mateus E.; Lacquagni, Riccardo; Bertoglio, Barbara; Bertolotti, Andrea; Tamellini, Gaia; Morini, Luca; Javan, Gulnaz T.; Setti, Ilaria; Visonà, Silvia D. (Frontiers in Psychiatry, 2024)
The high rate of incarceration, now exceeding 11.5 million people worldwide, has raised concerns about the conditions within penal institutions, such as the consequences of incarceration on a person’s health. This retrospective study aims to investigate the issue of death in custody, exploring the relationship between incarceration, health vulnerabilities, and death from the forensic pathologist’s point of view. We analyzed, from a forensic, clinical and toxicological perspective, 86 cases of deaths in detention facilities in North-Western Italy from 1999 to 2022. The analysis has shown that suicide, mainly committed by hanging, plastic bag suffocation and butane intoxication, represents the leading type of violent death (52%), followed by accidental deaths (16%). On the other hand, cardiovascular diseases are the leading cause of natural deaths (42%), followed by infectious diseases (especially HIV-related). The present study identifies the most frequent and critical situations and risk factors related to death in custody and the profile of the inmate who is at a higher risk of death, allowing to highlight the issues to be addressed from a public health point of view. On the whole, such findings call for comprehensive preventive measures, aligned with international human rights standards, addressing mental and physical care gaps, improving correctional officers' education and training, and focusing on inmates’ rehabilitation, well-being and dignity.